2019
DOI: 10.1111/jsr.12861
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effect of obstructive sleep apnea and periodic limb movements during sleep on heart rate variability

Abstract: Summary We aimed at assessing cardiac autonomic function by heart rate variability during sleep in patients with obstructive sleep apnea and periodic limb movements during sleep, and to compare it with that of patients with obstructive sleep apnea only, periodic limb movements during sleep only, and controls. We also aimed at investigating the interaction effect between apnea–hypopnea index and periodic limb movement index on heart rate variability. Four groups of patients (n = 42 each, total = 168) were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
(65 reference statements)
2
3
0
Order By: Relevance
“…Moreover, given that the 'A' regions probably masked the SA regions in this subject, and that either of them would have had a similar effect on the HR, it is also less likely here that the 'A' regions from this subject would be misclassified. Aside from that, interestingly, as published by a recent (2019) paper, it has been found that, for individuals with PLM and SA (as was the case for the subject being analyzed here), that the HR, i.e., reflecting the autonomic system, would have a 'synergistic' effect [68]. In other words, rather than for individuals with PLM or SA alone, the HRV parameters in their study (the LF-based feature, for example) for individuals with both PLM and SA were found to be higher [68].…”
Section: Analysis Of Classification Results Between the Normal And Abnormal Groupssupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, given that the 'A' regions probably masked the SA regions in this subject, and that either of them would have had a similar effect on the HR, it is also less likely here that the 'A' regions from this subject would be misclassified. Aside from that, interestingly, as published by a recent (2019) paper, it has been found that, for individuals with PLM and SA (as was the case for the subject being analyzed here), that the HR, i.e., reflecting the autonomic system, would have a 'synergistic' effect [68]. In other words, rather than for individuals with PLM or SA alone, the HRV parameters in their study (the LF-based feature, for example) for individuals with both PLM and SA were found to be higher [68].…”
Section: Analysis Of Classification Results Between the Normal And Abnormal Groupssupporting
confidence: 62%
“…Aside from that, interestingly, as published by a recent (2019) paper, it has been found that, for individuals with PLM and SA (as was the case for the subject being analyzed here), that the HR, i.e., reflecting the autonomic system, would have a 'synergistic' effect [68]. In other words, rather than for individuals with PLM or SA alone, the HRV parameters in their study (the LF-based feature, for example) for individuals with both PLM and SA were found to be higher [68]. Hence, it isn't unexpected that the HR changes depicted in the longitudinal HR subplot (shown in Figure 4.17) for the subject here was distinct in that, the HR changes corresponding to the segmented PLM (possibly masking the SA regions) were clearly high (in the case of LFiA) or low (in the case of HFiA).…”
Section: Analysis Of Classification Results Between the Normal And Abnormal Groupssupporting
confidence: 62%
“…A previous study reported that patients with PLMS plus OSAS have better sleep efficiency than those with PLMS alone (Iriarte et al, 2009). Conversely, recent evidence has indicated that PLMS and OSAS would have interactive effects on greater sleep fragmentation and greater sympathetic excitation compared with PLMS or OSAS alone (Li et al, 2019). Given the limited sample size and insufficient statistical power, we were unable to divide patients into more groups, including patients with PLMS plus OSAS, patients with PLMS or OSAS alone, and controls without PLMS or OSAS (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, recent evidence has indicated that PLMS and OSAS would have interactive effects on greater sleep fragmentation and greater sympathetic excitation compared with PLMS or OSAS alone (Li et al, 2019). Given the limited sample size and insufficient statistical power, we were unable to divide patients into more groups, including patients with PLMS plus OSAS, patients with PLMS or OSAS alone, and controls without PLMS or OSAS (Li et al, 2019). As a result, we could not assess the interactive effect of PLMS and OSAS in increasing the burden of CSVD, which needs to be explored by large‐sample studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Both low-frequency power (LF) and LF-to-high-frequency power (HF) ratios consistently increased in OSA patients compared to healthy controls, pointing to a shift in the sympathovagal balance toward sympathetic hyperactivity [12][13][14][15]18]. Meanwhile, other studies have yielded somewhat inconsistent findings with regard to HF, an HRV parameter reflecting parasympathetic activity: decreased HF [8,[18][19][20][21] or increased HF [12,22] in OSA patients when compared to controls.…”
Section: Introductionmentioning
confidence: 96%